Nanocrystalline Perovskite Hybrid Photodetectors with High Performance in Almost Every Figure of Merit. (15th December 2017) - Lin, Yuanwei; Lin, Guoming; Sun, Baoyun; Guo, Xuefeng
Abstract: Conversion of photon into electron is a phenomenon of great importance in nature. Photodetectors based on this principle have immense potential applications at the frontiers of both scientific and industrial communities, thus affecting the daily life. Herein, a novel class of high‐quality organic–inorganic trihalide perovskite nanoscale hybrid photodetectors is presented based on carbon electrode−molecule junctions working at mild conditions. Almost every figure of merit with high performance, such as highest responsivity, highest photogain, high detectivity, high linear dynamic range, and a broad spectral response, could be achieved simultaneously in a single device under different biases. These significant achievements benefit from rational choices of novel energy loss‐prevented hybrid perovskite nanocrystals as active materials and optimized carbon electrode−molecule junctions as device architectures, which leads to a hybridization mechanism of photodiodes and photoconductors. These investigations demonstrate a useful photodetector platform that might lead to many future photoelectric conversion applications in the practical way. Abstract : A new class of photodetectors working at mild conditions by using organic–inorganic trihalide perovskites as active materials and carbon electrode−molecule junctions as device architectures is demonstrated. The high performances, such as highest responsivity, highest photogain, high detectivity, high linear dynamic range, and a broad spectral response, could be achieved simultaneously in a single device under different biases.